Aprendizaje colaborativo y su aporte en el rendimiento académico a estudiantes de la unidad educativa” León de Febres Cordero”, Parroquia San Juan, Provincia los Ríos - Moreira Murillo, Karina Rocío (2016)
Ecuadorian education is going through a major transition and transformation throughout its organizational structure, these changes are aimed preferentially to improving the quality of education students. In this sense the strategies of teaching and learning used by teachers in the classroom, are the fundamental tools of teaching, for this reason the Collaborative Learning appears as highly participatory ideal strategy, which involves the development of abilities and skills by participants to increase their knowledge and skills, and they are the protagonists of their own development and progress. This strategy of collaborative work provides students with skills that allow you to interact with their peers, while providing skills you build, discover, transform and enhance the conceptual and allow you to develop authentic performance in daily life. This research analyzes the achievements of the education system at the national, provincial and, especially, how collaborative work affects the academic performance of students